Governability, New Development, and Rural Economy at Sanankerto Village, Indonesia - La Ode Machdani Afala; Rachmad Gustomy (Universitas Sultan Ageng Tirtayasa, 2021)
Abstract: Study on village governance and economic development increases in many countries. This article explores village economic development in contemporary Indonesia, which includes one of the national development's priority agendas. Despite several challenges in terms of governance, some villages have proved successful in driving economic development. This article mainly discusses rural governability in enhancing successful economic development in Sanankerto Village, Malang Regency. The research uses a qualitative method with an approach of governability to understand the village's success. The findings show that the more successful a village is, the greater the village's challenge. The successful governance in economic development is significantly relied on the village governance's capability, which consists of environmental and social system supports, a sound governance system, and a participatory, open, and transparent governing relationship between stakeholders. Moreover, the village's new law has significantly given broad authority and budget allocation for economic village development. This article significantly contributes to promoting villages' economic development where adequate governance capacity is an essential factor for achieving it.Keywords: governability; village economy; BUM Desa; development; welfare.